Forest clearance and land use by early farmers in Europe: Insights from north Greek oral history. (10th December 2018) - Halstead, Paul
Abstract: European prehistorians have long debated whether Neolithic farmers, especially in temperate central and northern Europe, exploited cleared woodland for short-term 'slash-and-burn' crop husbandry or for cultivation of 'permanent' gardens/fields. Because empirical evidence was scarce and rather indirect, circumstantial arguments based on the relative costs and benefits of the two rival regimes have hitherto dominated this debate, but more direct archaeobotanical proxies for Neolithic crop husbandry (based on weed ecology and crop isotopes) now favour the predominance of intensively cultivated permanent plots. At the same time, it is argued from ongoing experimental cultivation at Forchtenberg in southern Germany that short-term slash-and-burn husbandry offers much better returns on both land and labour, at least on poor soils marginal for Neolithic cereals. This paper presents oral historical evidence for mid-twentieth century clearance and subsequent long-term cultivation of mixed deciduous woodland in the Pieria region of northern Greece. These data extend the sparse European ethnographic and historical record of manual clearance for crop husbandry to deciduous woodland of the northern Mediterranean, while also providing comparative material against which to evaluate experimental results. Pierian farmers achieved good cereal yields for many years on cleared woodland, with very limited use of fire, demonstrating the viability of a permanent-cultivation regime for early farmers in the north Mediterranean, but suitable land was scarce in Pieria and informants had no experience of the alternative slash-and-burn regime. Conversely, the Forchtenberg experiments have effectively tested only the slash-and-burn regime under soil pH conditions hostile to successful long-term cultivation. Evaluation of these experiments in the light of the Pierian data suggests that long-term cultivation of cleared woodland would have offered Neolithic famers better returns than slash and burn under good or neutral soil conditions. Comparison of the likely returns of the two rival regimes thus offers no grounds for questioning archaeobotanical indications of Neolithic permanent cultivation. The Pierian and Forchtenberg data agree, however, in suggesting that the time elapsed between clearance and reliable grain harvests, under either regime, may have been long enough to pose a significant challenge to the survival of pioneer Neolithic farmers, especially if these were colonists settling beyond 'commuting' distance from their previous homes.